Integrated Evaluation of Urban Transportation, Structural Performance, Environmental Impacts, and Human Safety in Developing Cities - Reza Pahlevi Munirwan; Putra Jaya, Ramadhansyah; Aizat Mohd Taib (Disaster in Civil Engineering and Architecture, 2025)
The Editorial Board is pleased to present Volume 2, Number 2 (October 2025) of the Disasters in Civil Engineering and Architecture journal. This volume two presents an integrated evaluation of urban transportation systems, structural performance, environmental impacts, and human safety in the context of developing cities. It synthesizes key findings from traffic noise assessment, intelligent traffic control, travel behavior analysis, and driver alertness to understand transportation efficiency and safety challenges. Structural investigations on reinforced concrete, recycled aggregate concrete, and seismic strengthening systems are examined to evaluate infrastructure resilience and economic viability. Environmental and disaster-related dimensions, including urban noise exposure and flood risk management, are also addressed to highlight sustainability concerns. By combining engineering performance, environmental quality, and human factors, this work provides a multidisciplinary perspective to support safer, more resilient, and sustainable urban development in rapidly growing cities.